2022
DOI: 10.1161/jaha.121.024375
|View full text |Cite
|
Sign up to set email alerts
|

IV Sotalol Use in Pediatric and Congenital Heart Patients: A Multicenter Registry Study

Abstract: Background There is limited information regarding the clinical use and effectiveness of IV sotalol in pediatric patients and patients with congenital heart disease, including those with severe myocardial dysfunction. A multicenter registry study was designed to evaluate the safety, efficacy, and dosing of IV sotalol. Methods and Results A total of 85 patients (age 1 day–36 years) received IV sotalol, of whom 45 (53%) had additional congenital cardiac di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…While an age-factor nomogram developed for patients < 2 years of age exists, reports of using higher dose strategies without a slow up titration for terminating and improving tachyarrhythmias have been reported, using both enteral and IV formulations. [17][18][19][20][21] This present study found that our institutional dose regimen is significantly higher than the age-factor nomogram dosing recommendation (p < .001) and does not utilize a slow up titration (Figure 1). The use of a higher-dose regimen as initial therapy would theoretically allow for a shorter time to control of the arrhythmia, and decreased hospital stay.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…While an age-factor nomogram developed for patients < 2 years of age exists, reports of using higher dose strategies without a slow up titration for terminating and improving tachyarrhythmias have been reported, using both enteral and IV formulations. [17][18][19][20][21] This present study found that our institutional dose regimen is significantly higher than the age-factor nomogram dosing recommendation (p < .001) and does not utilize a slow up titration (Figure 1). The use of a higher-dose regimen as initial therapy would theoretically allow for a shorter time to control of the arrhythmia, and decreased hospital stay.…”
Section: Discussionmentioning
confidence: 51%
“…However, concerns of QTc prolongation, pro‐arrhythmic effects, variable renal clearance, and limited pharmacologic data in neonates has resulted in variable dosing strategies. While an age‐factor nomogram developed for patients < 2 years of age exists, reports of using higher dose strategies without a slow up titration for terminating and improving tachyarrhythmias have been reported, using both enteral and IV formulations 17–21 …”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that intrave-nous sotalol is effective for refractory SVT. 50,51 An initial treatment dose of 30 mg/m 2 (without age nomogram adjustment) given over 15 minutes provides effective chemical cardioversion in most patients. 51 Emerging data show that ivabradine, a novel selective inhibitor of hyperpolarization-activated cyclic nucleotide-gated channels, appears to be a safe and well-tolerated medication that can induce suppression of SVT and restoration of sinus rhythm in children with refractory SVT.…”
Section: Initial Svt Treatmentsmentioning
confidence: 99%
“…Additional adverse effects of sotalol may include hypotension, bradycardia and AV block [7,8] . Nevertheless, since its approval, IV sotalol has been successfully and safely used in both adult and pediatric patient populations for the management of arrhythmias in acute and chronic settings [9,10,11,12] . Initiation of sotalol therapy with PO loading requires 5 successive oral doses over a 3-day hospital stay for monitoring, at an estimated cost of $2931.55 per day [13] .…”
mentioning
confidence: 99%